Awareness, use, motivations and methods of accessing genetic testing in 2022 in the United States - Makhnoon, Sukh; Lee, MinJae; Prasad, Tanushree; Badalamenti, Alexa; Gurley, Tami; Waters, Erika A.; Skinner, Celette Sugg (Frontiers in Genetics, 2024)
IntroductionAwareness, access, and use of clinical and direct-to-consumer (DTC) genetic tests has increased in recent years with documented disparities in these services. We provide updated data on test awareness and use, and report novel data on motivations and methods for accessing genetic tests.MethodsNationally representative data from the 2022 Health Information National Trends Survey (HINTS 6) were used to assess awareness and use of ancestry, personal trait, specific disease, and carrier testing by sociodemographic characteristics, examine reasons for undergoing tests, and methods of accessing them.ResultsOverall, 81.4% of respondents were aware and 40.0% had undergone testing. Only 10% of tests were ordered by genetic counselors, 80% of carrier and 65% of specific disease tests were ordered by other healthcare providers. Understanding family history was the most common reason for undergoing ancestry (72.2%) or personal trait tests (64.9%) whereas reasons such as doctor’s recommendation (53%–59%), learning more about disease risk (18%–50%), and carrier testing (76%) were common for undergoing disease risk tests and carrier tests. In contrast to ancestry, personal trait, and carrier testing, there were no racial, ethnic, income, or rural/urban difference in use of specific disease risk testing.DiscussionDiffusion of genetic tests into US society, although incremental, has made sizable increases in awareness, equitable use of specific disease tests but worsening socioeconomic inequality in DTC genetic test use. The study provides update on the state of genetic testing in the US and identifies groups that may need help accessing clinical genomic information and services.